1997
DOI: 10.1136/ard.56.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage markers in synovial fluid in symptomatic knee osteoarthritis

Abstract: Results-The aggrecan/COMP ratio was higher (P < 0.001) in the group with radiographic osteoarthritis than in the control group. Conclusions-The higher aggrecan/COMP ratios in osteoarthritis could reflect increased cartilage matrix turnover in osteoarthritis with predominant release of aggrecan fragments. Synovial fluid analysis of cartilage markers holds promise as a useful means of monitoring changes in the cartilage turnover in studies of pathogenic mechanisms in osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 13 publications
1
16
0
3
Order By: Relevance
“…However, in disease this pattern may become altered. The results in the present studies are in line with a previous investigation showing that elevated serum COMP levels are predictive of developing joint destruction in OA (Petersson et al, 1992;Sharif et al, 1995). This may reflect an increased synthesis as well as release of this protein, in intact or fragmented form, in the early stages of the disease process.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, in disease this pattern may become altered. The results in the present studies are in line with a previous investigation showing that elevated serum COMP levels are predictive of developing joint destruction in OA (Petersson et al, 1992;Sharif et al, 1995). This may reflect an increased synthesis as well as release of this protein, in intact or fragmented form, in the early stages of the disease process.…”
Section: Discussionsupporting
confidence: 94%
“…The protein binds collagens I/II and the non-collagenous domains of collagen IX Thur et al, 2001). Interestingly, elevated COMP levels in serum have been found to be predictive of developing joint destruction in OA (Petersson et al, 1992;Sharif et al, 1995). Cartilage intermediate layer protein (CILP), a monomeric protein that is particularly enriched in the middle to deep layer of the adult articular cartilage, has been identified and characterized (Lorenzo et al, 1998a,b).…”
Section: Introductionmentioning
confidence: 97%
“…Although the exact function of COMP in cartilage is not yet known, mutations in the COMP gene have been identified that are responsible for at least two forms of heritable osteoarthritis (OA), multiple epiphysial dysplasia [25], and pseudoachondroplasia [26]. Several previous studies have confirmed that serum and synovial fluid COMP levels in patients with OA were much higher than normal [27,28]. It has previously been demonstrated that serum COMP increases during arthritis development in collagen II induced arthritis (CIA) and pristaneinduced arthritis in rats, and this increase coincided with the development of cartilage damage [29,30].…”
Section: Discussionmentioning
confidence: 96%
“…COMP is a major cartilaginous matrix molecule that is likely to be retained in the construct, even though it is secreted by chondrocytes and found in the synovial fluid as well (Recklies et al, 1998;Petersson et al, 1997). It is a shortcoming of this study that COMP retained in the scaffold was not determined, although the macroporous scaffold allows a passive exchange of the matrix proteins with the environment, and a constant release rate of synthesized molecules into the medium is expected (Grad et al, 2003a, b;Alini et al, 2003;Lee et al, 2003Lee et al, , 2005aWernike et al, 2008).…”
Section: Article In Pressmentioning
confidence: 99%